A Schiff-base-type vanadyl complex grafted on mesoporous carbon nitride: a new efficient catalyst for hydroxylation of benzene to phenol. Issue 112 (28th October 2015) - Xu, Jie; Jiang, Quan; Shang, Jie-Kun; Wang, Yue; Li, Yong-Xin
Abstract : VO(acac)2 was grafted on mesoporous g-CN material as a Schiff-base-type complex, and showed high catalytic activity in direct hydroxylation of benzene to phenol. Abstract : Mesoporous graphitic carbon nitride (g-CN) was utilized as a new support to immobilize vanadyl(iv ) acetylacetonate ([VO(acac)2 ]). The immobilized vanadyl complex materials (VOac-CND) have been thoroughly characterized by various techniques including N2 adsorption–desorption, XRD, SAXS, TEM, Raman, FT-IR, XPS and benzene-TPD. The characterization results showed that [VO(acac)2 ] had been successfully grafted on the surface of g-CN via the reaction between the carbonyl group of the acetylacetonate ligand and the amino groups of g-CN and thus transformed into a Schiff-base-type complex. Moreover, after the immobilization of [VO(acac)2 ], the ordered natures of the mesoporous structures and graphitic structures of the g-CN support have been well retained. The immobilization temperature has been found to be sensitive to the immobilization effect. As heterogeneous catalysts, the immobilized catalysts exhibited high performances in the direct hydroxylation reaction of benzene to phenol, affording a maximum phenol yield of ca. 20.0%. The catalytically active site for hydroxylation was proposed as the grafted vanadyl complex while the mesoporous g-CN played a crucial role in activating benzene.